Archaeological research in the Petra Valley: preliminary remarks from the excavation at the Corinthian Tomb - Raffaele Ranieri (Ksiegarnia Akademicka Publishing, 2020)
Archaeological research in the Petra Valley: preliminary remarks from the excavation at the Corinthian Tomb